An Injectable Dual‐Function Hydrogel Protects Against Myocardial Ischemia/Reperfusion Injury by Modulating ROS/NO Disequilibrium. Issue 15 (23rd March 2022) - Hao, Tian; Qian, Meng; Zhang, Yating; Liu, Qi; Midgley, Adam C.; Liu, Yangping; Che, Yongzhe; Hou, Jingli; Zhao, Qiang
Abstract: Acute myocardial infarction (MI) is the leading cause of death worldwide. Exogenous delivery of nitric oxide (NO) to the infarcted myocardium has proven to be an effective strategy for treating MI due to the multiple physiological functions of NO. However, reperfusion of blood flow to the ischemic tissues is accompanied by the overproduction of toxic reactive oxygen species (ROS), which can further exacerbate tissue damage and compromise the therapeutic efficacy. Here, an injectable hydrogel is synthesized from the chitosan modified by boronate‐protected diazeniumdiolate (CS‐B‐NO) that can release NO in response to ROS stimulation and thereby modulate ROS/NO disequilibrium after ischemia/reperfusion (I/R) injury. Furthermore, administration of CS‐B‐NO efficiently attenuated cardiac damage and adverse cardiac remodeling, promoted repair of the heart, and ameliorated cardiac function, unlike a hydrogel that only released NO, in a mouse model of myocardial I/R injury. Mechanistically, regulation of the ROS/NO balance activated the antioxidant defense system and protected against oxidative stress induced by I/R injury via adaptive regulation of the Nrf2‐Keap1 pathway. Inflammation is then reduced by inhibition of the activation of NF‐ κ B signaling. Collectively, these results show that this dual‐function hydrogel may be a promising candidate for the protection of tissues and organs after I/R injury. Abstract : An injectable chitosan‐based hydrogel (CS‐B‐NO) is synthesized that could release nitric oxide (NO) in response to reactive oxygen species (ROS) stimulation and thereby modulate ROS/NO disequilibrium after ischemia/reperfusion (I/R) injury. Administration of CS‐B‐NO efficiently attenuates cardiac damage and adverse cardiac remodeling, promotes repair of the heart, and ameliorates cardiac function in a mouse model of myocardial I/R injury.